ICONOLOGY-ICONOGRAPHY OF ISLAMIC ARTS BY TITA RUBIES AND RISPULES AT THE EXHIBITION OF FRAGMENTS OF MODERN INDONESIAN ART AT OHD MUSEUM: IKONOLOGI-IKONOGRAFI SENI RUPA ISLAM KARYA TITA RUBI DAN RISPUL PADA PAMERAN FRAGMENTS OF MODERN INDONESIAN ART DI OHD MUSEUM - Khairi, Khairi (JURNAL Dasarrupa: Desain dan Seni Rupa, 2024)
ABSTRACT Islamic art, as a manifestation of culture, presents its distinctive style and carries the spirit of its time through its iconography and iconology, which not only serve as therapeutic media for religious buildings but also for works of painting. This study further elaborates on the iconology and iconography of contemporary Islamic art today through the works of Tita Rubi and Rispul in the "Fragments of Modern Indonesian Art History" exhibition at the OHD Museum. The issues to be discussed in this research include the patterns, themes, types, and socio-cultural contexts that shape the symbols in the works of Tita Rubi and Rispul in this exhibition. This research utilizes Erwin Panofsky's Iconology-Iconography theory and employs a qualitative method with a case study approach. Tita Rubi’s work (Bayang-Bayang yang Maha Kecil, 2022) and Rispul’s work (Gua Hira, 2017) are installation artworks with a new synthesis aesthetic paradigm. Tita Rubi's work addresses gender issues in Indonesian society, while Rispul's work reflects phenomena related to human existence in life. Both works showcase new iconography within the context of contemporary Islamic art and are an important part of the fragments of the history of modern Indonesian art, continuing the legacy of modern Indonesian Islamic art from earlier figures like AD Pirous, Syaiful Adnan, Ahmad Sadali, and Amang Rahman. Keywords: Art, Islam, Contemporary, Tita Rubi, Rispul, OHD Museum